2019
DOI: 10.1101/747329
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual working memory representations in visual and parietal cortex do not remap after eye movements

Abstract: 10 11 Highlights 12 • Visual working memory (VWM) representations do not remap after making 13 saccades 14 • Eye movement degrade VWM representations in early visual cortex, limiting 15 the role of early visual cortex in VWM storage 16 • Parietal cortex shows persistent VWM representations across saccades 17 2 ABSTRACT 18It has been suggested that our visual system does not only process stimuli that are 19 directly available to our eyes, but also has a role in maintaining information in VWM 20 over a period of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…First, memory contents could have directly been remapped (cf. 3,[15][16][17] ) to their future-relevant location (in which case we should have only found a future gaze bias). Second, when dealing with multiple memory contents, contents could be stored at the past location at first and the future location could be considered only after relevant memory content has been selected (in which case the past bias should have preceded the future bias).…”
Section: Discussionmentioning
confidence: 79%
“…First, memory contents could have directly been remapped (cf. 3,[15][16][17] ) to their future-relevant location (in which case we should have only found a future gaze bias). Second, when dealing with multiple memory contents, contents could be stored at the past location at first and the future location could be considered only after relevant memory content has been selected (in which case the past bias should have preceded the future bias).…”
Section: Discussionmentioning
confidence: 79%
“…We found that, even under stable fixation, SF information became less retinotopically specific over time, from ∼150 ms after stimulus onset, leading to “emerging nonretinotopy” ( Melcher and Morrone, 2015 ). This suggest that, in addition to “retinotopically lingering attention” ( Golomb et al, 2010 ), emerging nonretinotopy of feature information could allow presaccadic and postsaccadic information to be combined and support trans-saccadic perception without requiring predictive remapping in early visual processing areas ( Irwin, 1992 ; He et al, 2019 ), since higher brain areas could read out the SF of the stimulus during the entire interval. Combined with the availability of gaze position information in early visual areas ( Morris and Krekelberg, 2019 ), low-level visual information could, in theory, be read out in head-centered coordinates continuously across a saccade ( Andersen et al, 1985 ; Pouget and Sejnowski, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite these findings, there are also several studies that reported an absence of spatiotopic effects (Knapen et al, 2009, Mathôt & Theeuwes, 2010He, Ekman, & A., & de Lange, F, , 2019;Lescroart, Kanwisher, & Golomb, 2016). Together, these different sets of findings argue against a version of spatiotopic processing that is omnipresent in visual perception across saccades.…”
Section: Discussionmentioning
confidence: 96%